Development of a Wall System Made with Thermally Optimized Masonry and Super Insulation Mortar Render - Rui Sousa (2019)
One aim from this nationally funded construction industry research project entitled "Efficient Plus Wall", was to develop a sustainable and energy-efficient non-structural wall system. The main objective, however, was to develop a lightweight masonry wall incorporating an external "thermal" render which optimised both thermal and mechanical resistances in external walls. The masonry is made with a vertical perforated lightweight concrete unit (O-Unit), which was thermally improved through topology/shape optimization and by using an open structure lightweight concrete as base material. The external rendering comprises a super insulation mortar (SIM) formulation currently in development and based on mineral binders, aerogel and other thermal insulation aggregates. The research results obtained from numerical simulations and experimental testing are presented and discussed, and highlight the mechanical and thermal characteristics of the thermal render, lightweight concrete units and masonry, including development aspects of their base materials. Although some adjustments to the base materials in developing appropriate mechanical and thermal properties are still needed, the results obtained are promising and in good agreement with the main objectives of the research project. (c) 2019, International Masonry Society. All rights reserved.